Estimation of Vertical Jump Height Using Nintendo Wii Remote IR Camera - Bhanupol Klongratog; Warit Pengto; Todsaporn Wornkert; Anupong Srongprapa (My University, 2018)
In this article, we proposed to measure the heights of countermovement jumps which are recorded in term of vertical leap by using the Wii Remote infrared camera. According to the physical principles, positions of the movement were detected based on the rules regarding conservation of energy, motion under gravity, and coordinate system. The obtained results were compared with that of the slow-motion measurements. The experiment involved 30 basketball players whose jump results were slightly deviated from the vertical measurement of the coordinate system. Therefore, the results should be calibrated each time the new system is installed.
Keywords: Countermovement; Basketball; Sports Dynamics and Biomechanics